Improving The Student’s Listening Skill By Notagy (Note Taking Strategy ) For The Twelfth Graders At SMK PGRI 2 Nganjuk - Henny Roesellaningtias (STKIP PGRI Nganjuk, 2019)
Listening is one of the most difficult tasks of language. Listening is an active process of selecting and interpreting information from auditory and visual clues. Listeners remember the beginning of the sentence while proceeding to the end. It is difficult for the students to memorize well when they do listening task activity. The research thinks that the students need something to help them to memorize what they have been listened two seconds is not enough for them to remember what they have listened to answer some questions prepare for them. Note taking strategy helps students to write notes as they follow some spoken text. It will help them comprehend the message of the text. These notes can be in skeleton form or free form.(Vandergrift,L 1997). The researcher tries to conduct improving the student’s listening skill by Notagy ( note taking strategy) in doing the listening activities of the twelfth grade at SMK PGRI 2 Nganjuk. This research uses classroom action research that covered planning, action, observation and reflection stage in cycle. The object of the research is XII accounting 1 which has 31 students. In Planning Stage, the teacher explained the students’ problem, especially in listening during teaching-learning process. The researcher was helped by colaborator who collected the note from teaching-learning process, the detail lesson plan for teaching listening was made to gain a better result. The data collection technique will be conducted by documentation, test, observation, and unstructured interview. The procedure of the research are: (1) identification of problem. (2) preparation,(3) arranging the action plan, (4) implementing of action,(5) observing and (6) making report. The researcher conducted in two cycles that are The researcher conducted in two cycles that are: planning, acting , observing and reflecting by twice meeting. Based on the analysis and discussing the researcher concluded that Notagy (Note taking strategy) can improve the students listening skill. It happened because the researcher tried to conduct: (1)Implementing the Notagy strategy in teaching listening, and (2), giving motivation to listen more even though by their mobile phone as alternative media to implement notagy by themselves.